Peningkatan Kemampuan Berpikir Kreatif Matematis Siswa Melalui Model Collaborative Learning Berbantuan Multimedia Interaktif - Alifa, Suci; Fajriana, Fajriana; Hidayatsyah, Hidayatsyah (Jurnal Ilmiah Kanderang Tingang, 2025)
The background of this research is the low level of students' mathematical creative thinking skills, particularly in the topic of quadrilaterals at SMP Negeri 1 Simpang Mamplam. Initial test results showed that many students had not met the indicators of fluency, flexibility, and originality in mathematical creative thinking. Contributing factors include teacher-centered pedagogy, declining interest in mathematics, and inadequate use of engaging and interactive learning resources. This study aims to determine whether the improvement in students’ mathematical creative thinking skills through the application of a collaborative learning model assisted by interactive multimedia is better than that achieved using a conventional model in learning quadrilaterals at SMP Negeri 1 Simpang Mamplam. The collaborative learning model is designed to encourage students to collaborate, exchange ideas, and be more active and motivated in the learning process with the help of interactive multimedia designed using Canva. This research is expected to benefit teachers, students, schools, and researchers, particularly in enhancing the quality of mathematics education and students’ mathematical creativity.